The importance of informal planning in Greece - Irini Frezadou (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
The long lasting unsolved spatial problems and the lack of a sustainable integrated transport system in Greece indicate the insufficiency of the formal planning procedures. For such complex problems, the complementary use of informal processes, like the test planning process, is especially useful. In 2015, at the initiative of ETH Zurich, three European universities (ETH Zurich, University of Patras, and National Technical University of Athens) collaborated on the pilot implementation of the test planning process revolving around the issue of the railway and spatial development in Patras, the third largest city on the Peloponnese. Such an attempt to use informal planning methods in the rather conventional milieu of Patras was directed towards creating a new planning culture in Greece. Furthermore, such a European project that enhances international cooperation and the transfer of know-how finally leads to the strengthening of European cohesion, a vital goal of any international project. – – Die seit langem ungelösten raumplanerischen Probleme und das Fehlen eines nachhaltigen integrierten Verkehrssystems zeigen, dass die formalen Planungsverfahren in Griechenland unzureichend sind. Bei derartigen komplexen Problemstellungen ist die Integration informeller Prozesse, wie z. B. Testplanungen, von besonderem Nutzen. Im Jahr 2015 arbeiteten auf Initiative der ETH Zürich drei europäische Universitäten (ETH Zürich, University of Patras und National Technical University of Athens) an der versuchsweisen Umsetzung einer Testplanung rund um das Thema Eisenbahn und Raumentwicklung in Patras, der drittgrößten Stadt auf dem Peloponnes. Dieser Versuch, informelle Planungsmethoden im eher konservativen Milieu von Patras zu nutzen, zielte darauf ab, eine neue Planungskultur in Griechenland zu etablieren. Darüber hinaus führt dieses europäische Projekt, das die internationale Zusammenarbeit und den Know-how-Transfer fördert, schließlich zur Stärkung des europäischen Zusammenhalts als wichtigem Ziel internationaler Vorhaben.
urn:nbn:de:0156-0952151; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; transport; spatial development; formal/informal planning; test planning process; planning culture; Patras; Greece; Verkehr; Raumentwicklung; formelle/informelle Planung; Testplanungsprozess; Planungskultur; Patras; Griechenland